THE REFLECTION OF DIDACTICAL DESIGN RESEARCH LEARNING AS AN EFFORT OF ELEMENTARY SCHOOL TEACHER EDUCATION (ESTE) LECTURERS’ PROFESSIONAL DEVELOPMENT - Duhita Savira Wardani; Medita Ayu Wulandari; Zaqiyah Lailatul Farihah (Jurnal Cakrawala Pendas, 2024)
The determining factors for the success of the learning process are students and the teacher/lecturer as the person most responsible for implementing the learning process. This study aimed to describe the process of learning reflection as the professional development of Elementary School Teacher Education (ESTE) lecturers based on Didactical Design Research (DDR) in learning the Elementary Science Basic Concepts course. The method used in this research is qualitative. The research design used is phenomenology. This research was conducted at the ESTE Study Program, one of the tertiary institutions in Cimahi City. The participants in this study were an ESTE lecturer. Data collection techniques used in this study were participant observation, interviews, and focus group discussions. The data analysis technique used was Interpretative Phenomenological Analysis (IPA). The results showed that there were several learning obstacles in the form of epistemological obstacles, which occurred due to students' lack of knowledge related to the concepts they were learning and caused students to experience misconceptions. Then a hypothetical learning trajectory is compiled as a series of learning paths that students go through to achieve more meaningful learning goals. The limitation in this study is that the analysis of each step in the DDR process has not been fully described, so that for further research each step can be clearly described to see a more real impact from the lecturer professional development process that has been implemented.